Identification of Sonneratia alba J. E. Smith endophytic fungi and its antagonists potential to the fungi Alternaria Alternata (Fr.) Keissler - Angkur, Reinardus Bonfilio; Sudirga, Sang Ketut; Hardini, Junita (Jurnal Biologi Udayana, 2025)
Alternaria alternata is the fungal pathogen that causes early blight disease in tomato plants which results in production declines of up to 79% in several countries. An alternative biocontrol solution to overcome this problem can utilize endophytic fungi associated with mangrove plants. Sonneratia alba mangrove plant has many bioactive compounds and endophytic fungal strains which have been widely used in the agricultural and pharmacological fields. This research aims to identify endophytic fungi from S. alba and determine their ability to inhibit the growth of A. alternata fungi. The results of the research identified 5 species, one of them is Penicillium sp. with the highest inhibition against A. alternata namely 73.96 ± 2.24%. Filtrate of the endophytic fungus Penicillium sp. significantly (P?0.05) showed the greatest inhibitory power at a concentration of 100% (v/v) against A. alternata colonies, namely 37.76 ± 1.97%. Based on these results, it can be concluded that the filtrate of Penicillium sp. KPM-2.1 fungus is less effective as an antagonist of A. alternata than filtrate of the comparative endophytic fungus Trichoderma harzianum KPD-1, which is 72.64 ± 1.90%.